Ultra-fast light-field microscopy with event detection - Liheng Bian; Xuyang Chang; Hanwen Xu; Jun Zhang (Light: Science & Applications)
Abstract The event detection technique has been introduced to light-field microscopy, boosting its imaging speed in orders of magnitude with simultaneous axial resolution enhancement in scattering medium.